2018
DOI: 10.3390/ijms19061800
|View full text |Cite
|
Sign up to set email alerts
|

MK-0677, a Ghrelin Agonist, Alleviates Amyloid Beta-Related Pathology in 5XFAD Mice, an Animal Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive deficits, neuroinflammation, and neuronal death. The primary pathogenic cause is believed to be the accumulation of pathogenic amyloid beta (Aβ) assemblies in the brain. Ghrelin, which is a peptide hormone predominantly secreted from the stomach, is an endogenous ligand for the growth hormone secretagogue-receptor type 1a (GHS-R1a). MK-0677 is a ghrelin agonist that potently stimulates the GHS-R1a ghrelin receptor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 100 publications
(110 reference statements)
1
25
2
Order By: Relevance
“…However, we note that a control protein, such as human IgG should, in future, be used to present the specific effect of LBP on amyloid formation, to further elucidate the physiological processes discussed in this paper. In future, our hypothesis could also be tested in a transgenic murine model of AD (TgAD) or the 5xFAD (amyloid over-producing) model or equivalent ( Vale et al, 2010 ; Jeong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that a control protein, such as human IgG should, in future, be used to present the specific effect of LBP on amyloid formation, to further elucidate the physiological processes discussed in this paper. In future, our hypothesis could also be tested in a transgenic murine model of AD (TgAD) or the 5xFAD (amyloid over-producing) model or equivalent ( Vale et al, 2010 ; Jeong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…GHSR1α may be a target for AD treatment. GHSR1α agonists such as MK0677 and LY444711 showed protective effects in animal and cell models (102,103). However, clinical trials of MK0677 in AD patients failed to show clinical benefit.…”
Section: Aβ Interact With Hippocampal Ghrelin/ghsr1α Signaling In Admentioning
confidence: 99%
“…Recent findings identify MK-0677, a synthetic GHS-R agonist that crosses the BBB, as a potential therapeutic cognitive enhancer as it promoted the accumulation of α-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid (AMPA) receptor on excitatory hippocampal synapses and improved long term potentiation (LTP) 59 . Moreover, Jeong et al 110 showed that MK-0677 ameliorated Aβ deposition, neuroinflammation, and neurodegeneration in the 5xFAD mouse model of AD. In the APPSwDI mouse model of AD the GHS-R agonist, LY444711, improved spatial memory performance 111 .…”
Section: Acyl-ghrelin Treatment Increases Adult Hippocampal Neurogenesismentioning
confidence: 99%